2021
DOI: 10.3390/curroncol28050351
|View full text |Cite
|
Sign up to set email alerts
|

Exercise to Reduce Anthracycline-Mediated Cardiovascular Complications in Breast Cancer Survivors

Abstract: While developments in cancer therapeutics have greatly reduced morbidity and mortality in females with breast cancer, it comes at a cost of an increased risk of cardiovascular complications. In particular, anthracyclines, like doxorubicin, which are a mainstay of current chemotherapy regimens, are associated with dose-dependent cardiotoxicity. Exercise has been widely accepted as an effective intervention in reducing cardiovascular risk in a variety of different clinical conditions. However, the benefits of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 64 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Lifestyle interventions, such as exercise, were also reported to be a preventive strategy for reducing DCM. Encouraging evidence in clinical studies showed that aerobic and resistance exercises improve systolic function and cardiorespiratory fitness in patients undergoing anthracycline treatment [125]. Innovative approaches targeting mitochondrial derangements may be developed in the near future.…”
Section: Perspectivesmentioning
confidence: 99%
“…Lifestyle interventions, such as exercise, were also reported to be a preventive strategy for reducing DCM. Encouraging evidence in clinical studies showed that aerobic and resistance exercises improve systolic function and cardiorespiratory fitness in patients undergoing anthracycline treatment [125]. Innovative approaches targeting mitochondrial derangements may be developed in the near future.…”
Section: Perspectivesmentioning
confidence: 99%
“…In addition, Alihemmati et al demonstrated that high intensity interval training in rats treated with doxorubicin led to a reduction in pro-apoptotic proteins, such as BAX and caspase 6, and overall fewer apoptotic cells compared to controls (57). Other pre-clinical studies have shown the benefit of exercise in reducing ROS production, increased gene expression of antioxidant molecules, reduced mPTP susceptibility, increased mitochondrial resilience, and lowered lipid peroxidation in rat models of AIC (58). A variety of pre-clinical studies demonstrated that swimming, forced treadmill and wheel running exercise programs reduced fibrosis and necrosis, decreased myocardial inflammatory markers, and protected against loss of cardiomyocytes and myofibrils among rodents exposed to doxorubicin (59).…”
Section: Aerobic Exercisementioning
confidence: 99%
“…Evidence has identi ed that women living with and after cancer are burdened with various adverse physical and psychological consequences from the conditions and associated treatments (Iddrisu et al, 2020;Joshy et al, 2020). In addition to concomitant problems such as osteoporosis (Shapiro, 2020), cardiovascular diseases (Bansal et al, 2022;Dhir & Sawant, 2021;Varghese et al, 2021), or secondary cancers (Demoor-Goldschmidt & de Vathaire, 2019; Roy et al, 2018), they commonly encounter manifestations such as pain (Van Den Beuken- Van et al, 2016), menopausal-like symptoms (Carpenter et al, 2014;Marino et al, 2014), sleeping disorders (Pai et al, 2020), anxiety, sadness, post-traumatic stress disorder (PTSD), and fear of cancer recurrence (Carreira et al, 2018;Niedzwiedz et al, 2019;Tsai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%